The Effect of Epigallocatechin Gallate Extract on Dental Erosion an in Vitro Study - Ayesha Iftikhar, Shafaq Zafar, Saifullah Khan Khalil, Syed Muhammad Awais, Shahida Batool, Muhammad Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the antierosive effect of epigallocatechin gallate extract (EGCG) on dental erosion and to compare it with potassium nitrate containing mouthwash. Materials and Methods: This invitro study was conducted in Sardar Begum Dental College and Peshawar dental hospital, Peshawar, KPK. The Scanning electron microscope study was carried out in Centralized Resource Laboratory (CRL), University of Peshawar while Microhardness in University of Engineering and Technology (UET), Peshawar. Total 042 healthy human premolars and impacted third molars were divided into 3 groups: Group I as control (distilled water), Group II was treated with potassium nitrate containing mouthwash while Group III was treated with EGCG. The samples were placed in artificial saliva for six hours. Afterwards teeth were placed in 10ml of the respective test solutions (For each group) for 4 minutes. Samples were kept in commercial beverage for fifteen min with constant stirring at (20-25 °C) afterwards washed with distilled water and then placed in artificial saliva for an hour. The process of erosion was done in four cycles. Finally, the samples were kept in deionized water. The samples were then subjected to Scanning Electron Microscopy (SEM), and micro-hardness.Averages were taken for statistical analysis.LSD post hoc (ANOVA) test was done for analysis of the groups. Results: There was detectable difference in the dentinal tubule occlusion and hardness between the three groups. EGCG and Potassium nitrate containing mouthwash yielded better results. Conclusion: It was concluded from the present study that EGCG and potassium nitrate demonstrated antierosive effects. Keywords: Dentin hypersensitivity, Dentinal Tubule, Potassium nitrate, EGCG